HAKIKAT ALAM SEMESTA, DAN PERAN MANUSIA SEBAGAI KHOLIFAH DI ALAM SEMESTA - Muhammad Nur Hadi; Achmat Mubarok (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2021)
The created universe is one of the signs of Allah's power. Not a few verses of the Qur'an invite us to reflect on His creation is no exception about the universe. Allah created humans and commissioned humans to perform imarah on earth by managing and maintaining it. As a caliph on earth, of course there are several principles that need to be considered by humans, namely first, the principle of responsibility for the universe and everything in it so that its sustainability is maintained. Second The principle of Compassion and Concern for Nature, humans should treat nature with a sense to love, cherish, and preserve the universe and all its contents, without discrimination and without domination.